Gig Economy During Pandemic in East Java - Hilman Hanivan; Suryo Adi Rakhmawan (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
The COVID-19 pandemic that hit Indonesia has harmed health, socially and economically. However, the pandemic has also indirectly become a catalyst for innovation, including in the employment sector including the Gig Economy. This study aims to describe the gig phenomenon in East Java, both in the form of gig workers and the gig economy during the new normal. Using data from the August 2021 National Labor Force Survey, this study then builds a model using binary logistic regression to determine the impact of the pandemic on workers' income or wages and working hours so that it is expected to be an analysis for the government to plan policies in the new normal. This study also builds a probability model using bayesian network analysis to determine the probability that gig workers will fall into the survival or by choice category. With the simulation image through the Bayesian model, the authorities can map out policies based on the variables used in the model. This research is empirical evidence that the gig economy is growing in East Java but raises problems related to gender discrimination and indications of wage differences between gig workers in the service sector and industry. The regression model that was built resulted in the conclusion that the working hours and wages of gig workers tend to be affected by the Pandemic. The handling can be started from the results of the Bayesian analysis, namely starting with female workers in urban areas because they have an excellent opportunity to be in the survival group of gig workers.